Protective agent for methanol synthesis catalyst and preparation method and application thereof
By using a catalyst protector with the support of Al2O3, SiO2 and M2Ox in the methanol synthesis catalyst, the fly temperature hazards and sintering problems caused by methanol activity in the prior art are solved, and the long-term stable operation of the catalyst and high-efficiency decarbonylated iron are achieved. Nickel capability.
Patent Information
- Application Number
- CN202111223460.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-10-20
AI Technical Summary
The existing methanol synthesis catalyst protectors have methanol activity during methanol synthesis, which may lead to potential fly temperature hazards and sintering problems, affecting the long-term stable operation of the device.
The catalyst protector with the support being Al2O3, SiO2 and M2Ox, wherein M is selected from B, Ge, As, Sb, Tb, and Po. The active parent and support are prepared by co-precipitation method, and beating, granulating and calculating to form CuO A catalyst with uniform distribution with ZnO increases the adsorption capacity and decomposition ability of carbonyl iron and carbonyl nickel.
It significantly reduces the activity of the protective agent on methanol, improves the adsorption capacity of carbonyl iron and carbonyl nickel, and ensures the long-term stable operation of the methanol synthesis catalyst, which is suitable for use in large-scale medium and low-pressure devices.
Smart Images

Figure CN115990484B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic material preparation, and in particular to a protective agent for a methanol synthesis catalyst and a preparation method and application thereof. Background Art
[0002] As an important basic chemical product, methanol is widely used in the fields of chemical industry, medicine, textile and light industry. In 2019, the domestic production capacity exceeded 87 million tons. In recent decades, in order to more effectively reduce the unit production cost of methanol, Lurgi Company first proposed the concept of Mega-methanol in 1997, and the large-scale methanol synthesis unit has become the development direction of the methanol industry. With the development trend of large-scale methanol, the original minor problems are gradually magnified.
[0003] With the trend of large-scale production equipment, carbonyl iron and nickel produced in methanol synthesis gas have become a problem that needs to be solved urgently, and the side effects they produce are also extremely obvious and multifaceted. Carbonyl iron and carbonyl nickel will cause the reaction to deviate from the main direction, trigger side reactions, and produce a variety of by-products, such as hydrocarbons and paraffins; these by-products will become impurities in methanol, affecting the purity of methanol, which not only brings difficulties to the distillation and extraction purification process, but also affects the product quality.
[0004] In order to ensure the long-term stable operation of the methanol synthesis device, it is imperative to develop a protective agent related to decarbonylation of iron and nickel. CN 110876935 A discloses a protective agent for a methanol synthesis catalyst, wherein the active center of the catalyst protective agent is composed of Cu and another metal active center M, and the remaining components include ZnO, Al2O3 and a molding agent, wherein M is one or two of alkaline earth metals, main group metals or transition metals Ca, Mg, Cr, Mn, Ti, Pb, Sn, and Sb. The protective agent for methanol synthesis catalyst mainly achieves the effect of increasing the capacity of decarbonylation of iron and carbonyl nickel in the protective agent by modifying the active center in the protective agent, but the protective agent still has methanol activity in the synthesis gas, which may cause a temperature runaway risk and cause the problem of sintering of the protective agent.
[0005] Therefore, there is an urgent need to provide a protective agent that does not affect the methanol synthesis process and can meet the long-term stable operation of industrial equipment. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem that the existing protective agent of methanol synthesis catalyst still has methanol activity, which affects the long-term stable operation of the methanol synthesis device, and to provide a methanol synthesis catalyst protective agent and its preparation method and application.
[0007] In order to achieve the above object, the present invention provides a protective agent for a methanol synthesis catalyst in a first aspect, wherein the protective agent comprises a carrier and an active component distributed on the carrier, the active component comprises CuO and ZnO, and the carrier comprises Al2O3, SiO2 and M2O x , wherein M is selected from at least one of B, Ge, As, Sb, Tb and Po, and x is the valence of M.
[0008] A second aspect of the present invention provides a method for preparing a protective agent for a methanol synthesis catalyst, wherein the method comprises:
[0009] Under the condition of pH value of 6.5-8.5, a solution containing copper salt and zinc salt is contacted with a first precipitant to perform a first coprecipitation reaction, and then the obtained precipitate is subjected to a first aging to obtain an active precursor;
[0010] Under the condition of pH value of 7.5-9.5, the solution containing aluminum salt, silicate and soluble M salt is contacted with a second precipitant to carry out a second coprecipitation reaction, and then the obtained precipitate is subjected to a second aging to obtain an active carrier;
[0011] The active matrix and the active carrier are mixed and then pulped, granulated and calcined in sequence;
[0012] Wherein, M is selected from at least one of B, Ge, As, Sb, Tb and Po.
[0013] The third aspect of the present invention provides a protective agent for a methanol synthesis catalyst prepared according to the method described in the second aspect.
[0014] A fourth aspect of the present invention provides a use of the protective agent for the methanol synthesis catalyst described in the first aspect or the second aspect in methanol synthesis.
[0015] Through the above technical scheme, the present invention can not only improve the activity of the active components and the adsorption capacity of carbonyl iron and carbonyl nickel by modifying the carrier in the protective agent, but also the protective agent has very low activity towards methanol during the methanol synthesis process and will not cause the risk of temperature runaway; it can protect the long-term operation of the methanol synthesis catalyst and is particularly suitable for use in large-scale medium and low pressure methanol synthesis equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 1 is the CO-TPD diagram of the protective agent in Examples 1-5 of the present invention and Comparative Example 1;
[0017] Figure 2 It is a graph showing the deironing performance of the protective agent of Example 1 of the present invention at different temperatures. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] As mentioned above, the first aspect of the present invention provides a protective agent for a methanol synthesis catalyst, the protective agent comprising a carrier and an active component distributed on the carrier, the active component comprising CuO and ZnO, the carrier comprising Al2O3, SiO2 and M2O x , wherein M is selected from at least one of B, Ge, As, Sb, Tb and Po, and x is the valence of M.
[0020] In the present invention, by modifying the carrier of the protective agent, not only the activity of the active component and the adsorption capacity of carbonyl iron and carbonyl nickel can be improved, but also the activity of the protective agent on methanol in the methanol synthesis process can be significantly reduced. The catalyst provided by the present invention is particularly suitable for use in large-scale methanol synthesis devices at medium and low pressures, that is, existing large-scale methanol industrial production devices at the million-ton level.
[0021] According to the present invention, preferably, M is selected from B or Tb.
[0022] In the present invention, the active components are uniformly distributed in the carrier in the form of multi-component oxides.
[0023] In some preferred embodiments of the present invention, based on the total amount of the protective agent, the content of Al2O3 is 0.01-10% by weight, for example, it can be 0.01% by weight, 0.05% by weight, 0.1% by weight, 0.2% by weight, 0.5% by weight, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, 4.5% by weight, 5% by weight, 5.5% by weight, 6% by weight, 6.5% by weight, 7% by weight, 7.5% by weight, 8% by weight, 8.5% by weight, 9% by weight, 9.5% by weight, 10% by weight % or any value in the range consisting of any two of the above values, preferably 1-5 wt %; the content of SiO2 is 0.1-20 wt %, for example, it can be 0.1 wt %, 0.5 wt %, 0.8 wt %, 1 wt %, 1.5 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 8 wt %, 10 wt %, 12 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20 wt % or any value in the range consisting of any two of the above values, preferably 8-18 wt %; M2Ox The content of the protective agent is 0.1-15% by weight, for example, 0.1% by weight, 0.5% by weight, 0.8% by weight, 1% by weight, 1.5% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 8% by weight, 10% by weight, 12% by weight, 14% by weight, 15% by weight or any value in the range of any two of the above values, preferably 10-15% by weight. Under the above preferred conditions, the activity of the protective agent to methanol can be further reduced and the adsorption capacity of the protective agent to carbonyl iron and carbonyl nickel can be improved.
[0024] According to the present invention, under preferred conditions, in the protective agent, Al2O3, SiO2 and M2O x The weight ratio is 1-5:3-15:5-15.
[0025] According to the present invention, under preferred conditions, in the protective agent, the weight ratio of the active component to the carrier is 60-75:20-35.
[0026] In some preferred embodiments of the present invention, in order to improve the adsorption and decomposition capacity of the protective agent for carbonyl iron and carbonyl nickel, the content of CuO is 2-80% by weight, based on the total amount of the protective agent, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any two of the above. The content of ZnO is 5-80% by weight, for example, it can be 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value in the range composed of any two of the above values, preferably 20-70% by weight.
[0027] The second aspect of the present invention provides a method for preparing a protective agent for a methanol synthesis catalyst, wherein the method comprises: preparing an active matrix (active component precursor) and an active carrier (carrier precursor) in the protective agent by a coprecipitation method, respectively, and then mixing the active matrix and the active carrier and calcining them; specifically, the method comprises:
[0028] Under the condition of pH value of 6.5-8.5, a solution containing copper salt and zinc salt is contacted with a first precipitant to perform a first coprecipitation reaction, and then the obtained precipitate is subjected to a first aging to obtain an active precursor;
[0029] Under the condition of pH value of 7.5-9.5, the solution containing aluminum salt, silicate and soluble M salt is contacted with a second precipitant to carry out a second coprecipitation reaction, and then the obtained precipitate is subjected to a second aging to obtain an active carrier;
[0030] The active matrix and the active carrier are mixed and then pulped, granulated and calcined in sequence;
[0031] Wherein, M is selected from at least one of B, Ge, As, Sb, Tb and Po.
[0032] According to the present invention, under preferred conditions, the conditions of the first coprecipitation reaction include: the pH value at the reaction endpoint is 6.5-8.5, and the temperature is 20-90°C; for example, the pH at the reaction endpoint can be 6.5, 6.8, 6.9, 7, 7.2, 7.3, 7.5, 7.6, 7.8, 7.9, 8, 8.2, 8.3, 8.5 or any value in the range composed of any two of the above values, preferably 6.5-8; the reaction temperature can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value in the range composed of any two of the above values; preferably 40-90°C.
[0033] According to the present invention, under preferred conditions, the conditions of the first aging include: a time of 10-120 min and a temperature of 20-90°C. The time of the first aging can be 10 min, 20 min, 25 min, 30 min, 40 min, 50 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 100 min, 105 min, 110 min, 120 min or any value in the range composed of any two of the above values; preferably 20-80 min.
[0034] According to the present invention, under preferred conditions, the conditions of the second coprecipitation reaction include: the pH value at the reaction endpoint is 7.5-9.5, and the temperature is 20-90°C; for example, the pH at the reaction endpoint can be 7.5, 7.8, 7.9, 8, 8.2, 8.3, 8.5, 8.6, 8.8, 8.9, 9, 9.2, 9.3, 9.5 or any value in the range composed of any two of the above values, preferably 7.5-8.5; the reaction temperature can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value in the range composed of any two of the above values; preferably 30-70°C.
[0035] According to the present invention, under preferred conditions, the conditions for the second aging include: a time of 10-120 min and a temperature of 20-90°C. The time for the second aging can be 10 min, 20 min, 25 min, 30 min, 40 min, 50 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 100 min, 105 min, 110 min, 120 min or any value in the range composed of any two of the above values; preferably 10-60 min.
[0036] The present invention has no special requirements for the types of the first precipitant and the second precipitant, as long as the pH value of the coprecipitation system can be controlled within the required range. Preferably, the first precipitant and the second precipitant are each independently selected from at least one of carbonate, bicarbonate and ammonia water.
[0037] In the present invention, calcination can effectively promote the decomposition of multi-component crystals and the distribution and migration of each metal oxide component while removing adsorbed water, lattice water and crystallization water, so as to obtain a metal composite oxide with uniform components. Preferably, the calcination conditions include: a temperature of 120-400°C and a time of 20-120min.
[0038] In some preferred embodiments of the present invention, the method further comprises: washing the active matrix precipitation system obtained by the first aging and the active carrier system obtained by the second aging, respectively, to obtain active matrix slurry and active carrier slurry, respectively.
[0039] In the present invention, the method further includes: mixing the active matrix slurry and the active carrier slurry and then slurrying them, letting the mixed system obtained by slurry stand, washing and drying; then molding the powder obtained by drying to obtain a protective agent; wherein the slurrying, washing, drying and granulation methods are all commonly known to those skilled in the art, and the present invention will not be repeated here.
[0040] In the present invention, when the protective agent is formed by tabletting, the method further comprises: mixing the above-mentioned dried product with an auxiliary agent (lubricant, forming agent) and then granulating; wherein the types of the lubricant and the forming agent can be known to technicians in the relevant field; for example, the lubricant can be graphite, and the forming agent can be at least one of water, aluminum sol and cellulose; in the present invention, the amount of the lubricant and the forming agent can be adjusted according to actual needs. Under preferred conditions, the total amount of the lubricant and the forming agent is 3-8wt% based on the total amount of the protective agent.
[0041] The third aspect of the present invention provides a protective agent for a methanol synthesis catalyst prepared according to the method described in the second aspect.
[0042] Preferably, the protective agent comprises a carrier and an active component distributed on the carrier, wherein the active component comprises CuO and ZnO, and the carrier comprises Al2O3, SiO2 and M2O x , wherein M is selected from at least one of B, Ge, As, Sb, Tb and Po, and x is the valence of M.
[0043] Preferably, based on the total amount of the protective agent, the content of Al2O3 is 0.01-10 wt%, the content of SiO2 is 0.1-20 wt%; x The content of CuO is 0.1-15% by weight, the content of ZnO is 2-80% by weight, and the content of ZnO is 5-80% by weight.
[0044] Preferably, in the protective agent, Al2O3, SiO2 and M2O x The weight ratio of the active component to the carrier is 1-5:3-15:5-15; the weight ratio of the active component to the carrier is 60-75:20-35.
[0045] A fourth aspect of the present invention provides an application of the protective agent for the methanol synthesis catalyst in methanol synthesis.
[0046] The present invention will be described in detail below through examples.
[0047] Example 1
[0048] Sodium carbonate solution (0.1 mol / L) was added to a 0.3 L mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration is 40g / L, Zn 2+ The concentration of the active precursor is 134 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 6.5 and the temperature is 40° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 40 min, and then washed with deionized water until the pH value of the filtrate is 6.5 to obtain an active precursor slurry;
[0049] Sodium carbonate solution (0.1 mol / L) was added to a mixed solution of 0.3 L aluminum nitrate, sodium silicate, and terbium nitrate (where Al 3+ The concentration is 4.5g / L, SiO3 2- The concentration of Tb is 6.33wt%. 3+The concentration of the active carrier is 14.5 g / L) and a second coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 7.2 and the temperature is 30° C. to obtain an active carrier precipitation system, the active carrier precipitation system is subjected to a second aging for 30 min, and then washed with deionized water until the end point pH value of the filtrate is 7.2 to obtain an active carrier slurry;
[0050] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 20 minutes, followed by suction filtration and drying. Graphite and water were added to the dried powder and pressed to obtain a protective agent A-1. The results are shown in Table 1.
[0051] Example 2
[0052] Sodium bicarbonate solution (0.5 mol / L) was added to a 0.2 L mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration of Zn is 32g / L. 2+ The concentration of the active precursor is 201 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 7.2 and the temperature is 60° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 30 min, and then washed with deionized water until the pH value of the filtrate is 7.2 to obtain an active precursor slurry;
[0053] Sodium bicarbonate solution (0.5 mol / L) was added to a mixed solution of 0.5 L aluminum nitrate, sodium silicate, and boron nitrate (where Al 3+ The concentration is 0.52g / L, SiO3 2- The concentration of B 3+ The concentration of the active carrier is 4.7 g / L) and a second coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 7.5 and the temperature is 50° C. to obtain an active carrier precipitation system, the active carrier precipitation system is subjected to a second aging for 50 min, and then washed with deionized water until the end point pH value of the filtrate is 7.5 to obtain an active carrier slurry;
[0054] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 30 minutes, followed by suction filtration and drying. Graphite and cellulose were added to the dried powder, and the powder was pressed to obtain a protective agent A-2. The results are shown in Table 1.
[0055] Example 3
[0056] Potassium carbonate solution (1.5 mol / L) was added to a 0.5 L mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration is 40g / L, Zn 2+The concentration of the active precursor is 93 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 7.2 and the temperature is 70° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 50 min, and then washed with deionized water until the pH value of the filtrate is 7.2 to obtain an active precursor slurry;
[0057] Potassium carbonate solution (1.5 mol / L) was added to a mixed solution of 0.6 L aluminum nitrate, sodium silicate, and antimony nitrate (where Al 3+ The concentration is 0.88g / L, SiO3 2- The concentration of Sb is 1.05wt%. 3+ The concentration of the active carrier is 4.2 g / L) and a second coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 8.5 and the temperature is 60° C. to obtain an active carrier precipitation system, the active carrier precipitation system is subjected to a second aging for 70 min, and then washed with deionized water until the end point pH value of the filtrate is 8.5 to obtain an active carrier slurry;
[0058] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 50 minutes, followed by suction filtration and drying. Graphite and aluminum sol were added to the dried powder, and the powder was pressed to obtain a protective agent A-3. The results are shown in Table 1.
[0059] Example 4
[0060] Sodium bicarbonate solution (2.5 mol / L) was added to 0.4 L of a mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration is 20g / L, Zn 2+ The concentration of the active precursor is 105 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 8 and the temperature is 80° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 80 min, and then washed with deionized water until the end point pH value of the filtrate is 8 to obtain an active precursor slurry;
[0061] Sodium bicarbonate solution (2.5 mol / L) was added to a mixed solution of 0.3 L aluminum nitrate, sodium silicate, and polonium nitrate (where Al 3+ The concentration is 0.86g / L, SiO3 2- The concentration of Po is 6.33wt%. 4+ The concentration of the active carrier is 17.3 g / L) and a second coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 9 and the temperature is 70° C. to obtain an active carrier precipitation system, the active carrier precipitation system is subjected to a second aging for 90 min, and then washed with deionized water until the end point pH value of the filtrate is 9 to obtain an active carrier slurry;
[0062] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 80 minutes, followed by suction filtration and drying. Graphite and cellulose were added to the dried powder, and the powder was pressed to obtain a protective agent A-4. The results are shown in Table 1.
[0063] Example 5
[0064] Add ammonia water (4 mol / L) to a 0.5 L mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration is 56g / L, Zn 2+ The active precursor precipitation system is subjected to a first coprecipitation reaction at a concentration of 48 / L, the pH of the reaction system is controlled to be 8 and the temperature is 90° C., and an active precursor precipitation system is obtained. The active precursor precipitation system is subjected to a first aging for 100 min, and then washed with deionized water until the end point pH value of the filtrate is 8, and an active precursor slurry is obtained;
[0065] Sodium bicarbonate solution (2.5 mol / L) was added to a mixed solution of 0.6 L aluminum nitrate, sodium silicate, and arsenic nitrate (where Al 3+ The concentration is 1.32g / L, SiO3 2- The concentration of As is 2.95wt%. 5+ The concentration of the active carrier is 5.97 g / L) and a second coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 9.5 and the temperature is 70° C. to obtain an active carrier precipitation system, the active carrier precipitation system is subjected to a second aging for 120 min, and then washed with deionized water until the end point pH value of the filtrate is 9.5 to obtain an active carrier slurry;
[0066] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 120 minutes, followed by suction filtration and drying. Graphite and water were added to the dried powder and pressed to obtain a protective agent A-5. The results are shown in Table 1.
[0067] Example 6
[0068] The method of Example 1 is different from that in the preparation process of the active carrier slurry, Al 3+ The concentration is 9g / L, SiO3 2- The concentration of Tb is 6.33wt%. 3+ The concentration was 7.25 g / L to obtain protective agent A-6. The results are shown in Table 1.
[0069] Example 7
[0070] The method of Example 1 is different from that in the preparation process of the active carrier slurry, Al 3+ The concentration is 0.45g / L, SiO3 2-The concentration of Tb is 6.33wt%. 3+ The concentration was 21 g / L to obtain protective agent A-7. The results are shown in Table 1.
[0071] Example 8
[0072] The method of Example 1 is different from that in the preparation process of the active carrier slurry, Al 3+ The concentration is 2.25g / L, SiO3 2- The concentration of Tb is 3.2wt%. 3+ The concentration was 7.75 g / L to obtain protective agent A-8. The results are shown in Table 1.
[0073] Comparative Example 1
[0074] The protective agent B-1 was obtained by following the method of Example 1, except that terbium nitrate was not added during the preparation of the active carrier slurry. The results are shown in Table 1.
[0075] Comparative Example 2
[0076] The method of Example 1 is followed, except that terbium nitrate is not added during the preparation of the active carrier slurry, and terbium nitrate is added during the preparation of the active matrix slurry, as follows:
[0077] Sodium carbonate solution (0.1 mol / L) was added to a 0.3 L mixed solution of copper nitrate, zinc nitrate and terbium nitrate (Cu 2+ The concentration is 40g / L, Zn 2+ The concentration is 134g / L, Tb 3+ The concentration of the active precursor is 14.5 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 6.5 and the temperature is 40° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 40 min, and then washed with deionized water until the end point pH value of the filtrate is 6.5 to obtain an active precursor slurry;
[0078] Sodium carbonate solution (0.1 mol / L) was added to 0.3 L of a mixed solution of aluminum nitrate and sodium silicate (where Al 3+ The concentration is 4.5g / L, SiO3 2- The concentration of the active carrier is 6.33wt%), and the pH of the reaction system is controlled to be 7.2 and the temperature is 30°C to obtain an active carrier precipitation system. The active carrier precipitation system is subjected to a second aging for 30min, and then washed with deionized water until the pH value of the filtrate is 7.2 to obtain an active carrier slurry.
[0079] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 20 minutes, followed by suction filtration and drying. Graphite and water were added to the dried powder and pressed to obtain a protective agent B-2. The results are shown in Table 1.
[0080] Comparative Example 3
[0081] The method of Example 3 is followed, except that antimony nitrate is not added during the preparation of the active carrier slurry, and antimony nitrate is added during the preparation of the active matrix slurry, as follows:
[0082] Potassium carbonate solution (1.5 mol / L) was added to a 0.5 L mixed solution of copper nitrate and zinc nitrate (Cu 2+ The concentration is 40g / L, Zn 2+ The concentration is 93g / L, Sb 3+ The concentration of the active precursor is 5.04 g / L) and a first coprecipitation reaction is carried out, the pH of the reaction system is controlled to be 7.2 and the temperature is 70° C. to obtain an active precursor precipitation system, the active precursor precipitation system is subjected to a first aging for 20 min, and then washed with deionized water until the pH value of the filtrate is 7.2 to obtain an active precursor slurry;
[0083] Potassium carbonate solution (1.5 mol / L) was added to 0.6 L of a mixed solution of aluminum nitrate and sodium silicate (where Al 3+ The concentration is 0.88g / L, SiO3 2- The concentration of the active carrier is 1.1wt%), and the pH of the reaction system is controlled to be 8.5 and the temperature is 60°C to obtain an active carrier precipitation system. The active carrier precipitation system is subjected to a second aging for 40 minutes, and then washed with deionized water until the end point pH value of the filtrate is 8.5 to obtain an active carrier slurry.
[0084] The active matrix slurry and the active carrier slurry were mixed and slurried, and then allowed to stand for 50 minutes, followed by suction filtration and drying. Graphite and cellulose were added to the dried powder and pressed to obtain a protective agent B-3. The results are shown in Table 1.
[0085] Comparative Example 4
[0086] The method of Example 1 is different in that the protective agent is prepared by a single coprecipitation method, as follows:
[0087] Sodium carbonate solution (0.1 mol / L) was added to a mixed solution of 0.3 L copper nitrate, zinc nitrate, aluminum nitrate, sodium silicate and terbium nitrate (Cu 2+ The concentration is 40g / L, Zn 2+ The concentration is 134 / L, Al 3+The concentration is 4.5g / L, SiO3 2- The concentration of Tb is 6.33wt%. 3+ The concentration of the active precursor is 14.5 g / L) and a co-precipitation reaction is carried out, the pH of the reaction system is controlled to be 6.5 and the temperature is 40° C. to obtain an active precursor precipitation system, the active precursor precipitation system is aged for 80 min, and then washed with deionized water until the pH value of the filtrate end point is 6.5 to obtain a precursor;
[0088] The precursor was slurried and then allowed to stand for 20 minutes, followed by suction filtration and drying. Graphite and water were added to the dried powder for compression molding to obtain a protective agent B-4. The results are shown in Table 1.
[0089] Comparative Example 5
[0090] The method of Example 1 is different from that in the preparation process of the active carrier slurry, Al 3+ The concentration is 13.5g / L, SiO3 2- The concentration of Tb is 2.1wt%. 3+ The concentration was 21 g / L to obtain protective agent B-5. The results are shown in Table 1.
[0091] Comparative Example 6
[0092] The method of Example 1 is different from that in the preparation process of the active carrier slurry, Al 3+ The concentration is 4.5g / L, SiO3 2- The concentration of Tb is 2.1wt%. 3+ The concentration was 29 g / L to obtain protective agent B-6. The results are shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] Note: *Weight ratio
[0097] Test Example 1
[0098] 2 mL of protective agents A-1 to A-8, B-1 to B-6 and 2 mL of methanol catalyst (C-307) were loaded into the protective agent evaluation device, and the synthesis gas mixed with carbonyl iron nickel was introduced. The reaction was carried out at 220°C for 6 hours. The carbonyl iron nickel content of the synthesis gas, the carbonyl iron nickel content in the protective agent body and the carbonyl iron nickel content in the methanol catalyst body were measured at the inlet and outlet. The experimental results are shown in Table 2 and Figure 2 shown.
[0099] The method for determining the content of carbonyl iron and nickel in the protective agent (total Fe / Ni capacity) is as follows: the reacted protective agent is immersed in an acid solution to fully and completely dissolve the carbonyl iron and carbonyl nickel in the protective agent, and the content of iron and nickel in the solution is measured by an ultraviolet spectrophotometer and ICP according to the relevant determination standards for the CuZnAl content of methanol synthesis catalysts.
[0100] The test method for the carbonyl iron nickel content in the methanol catalyst is the same as the method for the carbonyl iron nickel content in the protective agent.
[0101] Removal rate = (carbonyl iron nickel content of inlet synthesis gas - carbonyl iron nickel content of outlet synthesis gas) / carbonyl iron nickel content of inlet synthesis gas × 100%
[0102] Initial activity of protective agent methanol: 2 mL of protective agents A-1 to A-8, B-1 to B-6 were loaded into the protective agent evaluation device. The volume composition of industrial synthesis gas was: CO: 13%, CO2: 3%, H2: 65%, and the remaining nitrogen was balanced. The reaction temperature was 220°C. After stable operation for 2 hours, the alcohol was measured and the methanol yield (i.e., the initial activity of methanol) was calculated. The experimental results are shown in Table 2.
[0103] Table 2
[0104]
[0105] Note: ppm is volume content.
[0106] It can be seen from Table 2 that: compared with protective agents B-1 to B-6, the protective agents of Examples A-1 to A-9 of the present invention have a higher removal rate of decarbonylated iron and nickel, and the initial methanol activity can be reduced to 0, with basically no methanol activity, which can effectively ensure the longer operation of the methanol synthesis catalyst.
[0107] from Figure 2 In the figure, curve BHJ-12 refers to the iron capacity adsorbed in protective agent A-1 at different reaction temperatures, and curve C307 refers to the iron content absorbed in methanol catalyst C307 under the protection of protective agent A-1. Figure 2 It can be seen that as the temperature increases, the capacity of iron absorbed in the protective agent A-1 gradually increases, while the iron content in the methanol catalyst also decreases significantly, indicating that the protective agent A-1 has a good adsorption effect on iron and can better protect the methanol catalyst.
[0108] Test Example 2
[0109] CO-TPD: It is obtained by using the programmed temperature adsorption-desorption method. Pure CO gas is introduced into a reaction tube filled with a protective agent, and the CO content in the tail gas is continuously measured during adsorption and desorption.
[0110] from Figure 1It can be seen that the adsorption amount and adsorption intensity of CO by different protective agent samples are different. The larger the absorption peak area, the greater the adsorption amount of CO by the protective agent, and the higher the temperature, the higher the adsorption intensity of CO by the protective agent.
[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A protective agent for a methanol synthesis catalyst, characterized in that: The protective agent comprises a carrier and active components distributed on the carrier, wherein the active components comprise CuO and ZnO, and the carrier comprises Al2O3, SiO2 and M2O x , wherein M is selected from at least one of B, Ge, As, Sb, and Tb, and x is the valence of M; wherein, based on the total amount of the protective agent, the content of Al2O3 is 0.01-10 wt%, the content of SiO2 is 0.1-20 wt%, and the content of M2O x The content of is 0.1-15% by weight, the content of CuO is 2-80% by weight, and the content of ZnO is 5-80% by weight; The preparation method of the protective agent of the methanol synthesis catalyst comprises: contacting a solution containing a copper salt and a zinc salt with a first precipitant under a pH value of 6.5-8.5 to perform a first coprecipitation reaction, and then performing a first aging on the obtained precipitate to obtain an active matrix; Under the condition of pH value of 7.5-9.5, a solution containing aluminum salt, silicate and soluble M salt is contacted with a second precipitant to carry out a second coprecipitation reaction, and then the obtained precipitate is subjected to a second aging to obtain an active carrier; The active matrix and the active carrier are mixed and then pulped, granulated and calcined in sequence.
2. The protective agent according to claim 1, wherein Based on the total amount of the protective agent, the content of Al2O3 is 1-5% by weight; and / or, based on the total amount of the protective agent, the content of SiO2 is 8-18% by weight; And / or, based on the total amount of the protective agent, M2O x The content is 10-15% by weight.
3. The protective agent according to claim 1, wherein In the protective agent, Al2O3, SiO2 and M2O x The weight ratio is 1-5:3-15:5-15; And / or, the weight ratio of the active component to the carrier is 60-75:20-35.
4. The protective agent according to claim 1 or 2, wherein The content of CuO is 15-75% by weight, and the content of ZnO is 20-70% by weight.
5. A method for preparing the protective agent for the methanol synthesis catalyst according to claim 1, characterized in that: The method comprises: Under the condition of pH value of 6.5-8.5, a solution containing copper salt and zinc salt is contacted with a first precipitant to perform a first coprecipitation reaction, and then the obtained precipitate is subjected to a first aging to obtain an active precursor; Under the condition of pH value of 7.5-9.5, a solution containing aluminum salt, silicate and soluble M salt is contacted with a second precipitant to carry out a second coprecipitation reaction, and then the obtained precipitate is subjected to a second aging to obtain an active carrier; The active matrix and the active carrier are mixed and then pulped, granulated and calcined in sequence; Wherein, M is selected from at least one of B, Ge, As, Sb, and Tb.
6. The method according to claim 5, wherein: The conditions of the first coprecipitation reaction include: a temperature of 20-90°C; And / or, the first aging conditions include: temperature of 20-90° C. and time of 10-120 min.
7. The method according to claim 5 or 6, wherein: The conditions of the second coprecipitation reaction include: a temperature of 20-90°C; And / or, the second aging conditions include: temperature of 20-90° C. and time of 10-120 min.
8. The method according to claim 5 or 6, wherein: The first precipitant and the second precipitant are each independently selected from at least one of carbonate, bicarbonate and ammonia water.
9. The method according to claim 7, wherein: The first precipitant and the second precipitant are each independently selected from at least one of carbonate, bicarbonate and ammonia water.
10. The method according to any one of claims 5 to 6 and 9, wherein: The calcination conditions include: temperature of 120-400° C. and time of 20-120 min.
11. The method according to claim 7, wherein: The calcination conditions include: temperature of 120-400° C. and time of 20-120 min.
12. The method according to claim 8, wherein: The calcination conditions include: temperature of 120-400° C. and time of 20-120 min.
13. A protective agent for a methanol synthesis catalyst prepared by the method according to any one of claims 5 to 12.
14. Use of the protective agent for methanol synthesis catalyst according to any one of claims 1 to 4 and 13 in methanol synthesis.
